FAKTOR–FAKTOR YANG MEMPENGARUHI KUALITAS PENERAPAN LAPORAN KEUANGAN BERDASARKAN SAK ETAP PADA UMKM DI KOTA PALEMBANG. - Lis Djuniar; Yeni, Mesri (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2020)
This study aimed to determine the effect of educational educational bacground, level of education, business age, zise of business, and provision of information on the implementation of financial statements based on SAK ETAP in MSMEs in Palembang. This type of research was associative research. This research was conducted at the UMK in Palembang. The variables in this study were educational background, education level, business size, and provision of sociallization. The data used was primary data with data collection techniques namely questionnaires and interviews with 100 respondents. Based on the results of research conducted at the UMK in Palembang. Conclusions can be taken simultaneously that educational background, level of education, size of business, and provision of socialization had an influence and significant effect on the application of financial statments based on SAK ETAP, while partially background variables education, level of education, size of business, and provision of socialization had an influence and significant effect on the application of financial statments based on SAK ETAP.